2022
DOI: 10.3390/s22030885
|View full text |Cite
|
Sign up to set email alerts
|

Crack Detection in Frozen Soils Using Infrared Thermographic Camera

Abstract: Frozen soils are encountered on construction sites in the polar regions or regions where artificial frozen ground (AFG) methods are used. Thus, efficient ways to monitor the behavior and potential failure of frozen soils are currently in demand. The advancement of thermographic technology presents an alternative solution as deformation occurring in frozen soils generate heat via inter-particle friction, and thus a subsequent increase in temperature. In this research, uniaxial compression tests were conducted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The method of freeze sinking has been widely used in China to improve the soil strength and shaft wall stability during excavation (e.g. Wang et al [ 25 ]; Liu and Wang [ 26 ]; Zhao et al [ 27 ]). Systematic studies on the mechanical properties of frozen soils have been reported, which investigate the influences of temperature, stress condition, and the moisture content [ 28 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The method of freeze sinking has been widely used in China to improve the soil strength and shaft wall stability during excavation (e.g. Wang et al [ 25 ]; Liu and Wang [ 26 ]; Zhao et al [ 27 ]). Systematic studies on the mechanical properties of frozen soils have been reported, which investigate the influences of temperature, stress condition, and the moisture content [ 28 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The strength of frozen ground depends on temperature, porosity, water content, loading rate, and other factors, as shown in [11,[25][26][27][28]. All these factors inevitably affected the values of F peak and u peak in our model (14), so this model can be applied or adapted to other mechanical systems.…”
Section: Discussionmentioning
confidence: 99%
“…Digital cameras may not be able to capture micro-cracks in red brick due to pixel resolution. However, infrared thermal images can detect cracks through micro-cracks and the temperature difference between cracks and red bricks [38,39]. Therefore, in this paper, a thermal infrared camera was used to detect not only cracks, but also various objects present in the heritage building.…”
Section: Infrared Thermal Imagingmentioning
confidence: 99%